PENGARUHCORPORATE GOVERNANCE DAN PENGUNGKAPAN SUKARELAPADALIKUIDITAS SAHAM:STUDI EMPIRIS DI BEI - Susilowati, Retno Yuni Nur (Universitas Jember, 2011)
This research aims to get empirical evidences that there is influence of both corporate governance practices and voluntary disclosure on the firmsâ stock liquidity. Samples used in this research are nonfinancial companies listed in the Indonesia Stock Exchange (IDX) that participated in the CGPI (corporate governance perception index) surveys in the periods 2003-2008 performed by IICG (the Indonesian Institute for Corporate Governance). The hypotheses are tested by using multiple regression analysis. The results indicate that corporate governance and voluntary disclosure have positive effects on stock liquidity. It means the better the corporate governance and voluntary disclosure practices, the higher the stock liquidity is. This matter generates conclusion that investors notice corporate governance and voluntary disclosure practices conducted by companies. Keywords: corporate governance, voluntary disclosure, stock liquidity